Rancangan Sistem Manajemen Skripsi Berbasis Web Menggunakan Metode Rapid Application Development (RAD) - Novan Alkaf Bahraini Saputra; Harja Santana Purba (JURIKOM (Jurnal Riset Komputer), 2022)
This study aims to develop a thesis management system that can facilitate the management and monitoring of student thesis progress. For this reason, it is necessary to develop a web-based thesis management system that can handle these problems and is based online to facilitate access that is not limited to time and space. The thesis management system is made to serve the entire flow of thesis activities in the computer education study program, starting from the submission of topics, the seminar process, guidance to the assessment of the thesis trial. The design of the system uses the rapid application development ( RAD)  method. Design using UML, such as use case diagrams and activity diagrams, is equipped with entity relationship diagrams (ERD) and interface design using Figma. The technologies used are Laravel PHP Framework, Bootstrap, Javascript JQuery Library, and MySQL Database. Blackbox testing is carried out for all features in the system that are successfully run according to the scenario. 25 student respondents agreed that the thesis management system developed has ease of use and design accuracy. Testing the system generates data that the system is ready for use and implementation. So the system created is considered applicable to the FKIP ULM computer education study program